2022
DOI: 10.1029/2021jb023613
|View full text |Cite
|
Sign up to set email alerts
|

Olivine Morphology and Fabric During Diffusion Creep: Pure Shear Experiments

Abstract: The classic diffusion creep model predicts mass (atomic) transfer from grain boundaries that are normal to the high (compressional) stress direction to boundaries that are normal to the direction of low stress (Coble, 1963;Herring, 1950; Nabbaro, 1948). This process produces grains with anisotropic shapes that are often responsible for mineral lineations and foliations in deformed rocks (Passchier & Trouw, 2005). Based on experimental studies on fine-grained olivine aggregates, we recently reported the finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 55 publications
4
13
0
Order By: Relevance
“…Such a simple relationship holds for f II values of up to 0.35, which probably corresponds to the range in which the secondary grains are essentially isolated from each other (Equation 7). This relationship is predicted to also hold during diffusion creep, which has been confirmed experimentally (Kim et al., 2022; Tasaka & Hiraga, 2013).…”
Section: Grain Size and Viscosity Of Polymineralic Aggregates Deformi...supporting
confidence: 59%
See 1 more Smart Citation
“…Such a simple relationship holds for f II values of up to 0.35, which probably corresponds to the range in which the secondary grains are essentially isolated from each other (Equation 7). This relationship is predicted to also hold during diffusion creep, which has been confirmed experimentally (Kim et al., 2022; Tasaka & Hiraga, 2013).…”
Section: Grain Size and Viscosity Of Polymineralic Aggregates Deformi...supporting
confidence: 59%
“…We showed that the grain sizes of olivine and pyroxene in xenoliths follow the Zener relationship (Equation 7), which indicates that the sizes are determined by grain growth rather than the stress present during dislocation creep . The occurrence of dislocation creep has been interpreted based on the CPO of olivine (Liu et al, 2019); however, we have shown that the same CPO patterns can develop during diffusion creep (Kim et al, 2022;Miyazaki et al, 2013). Given that a 1-mm grain size corresponds to the size in the last phase of horizontal flow in the bottom of the lower mantle and that the flow continues for ∼100 million years (= t) (Equation 21a) during which we can assume constant temperature and pressure, the dt viscometer gives a η of ∼10 19 Pa•s (Figure 20).…”
Section: Applications Of Grain Size-time Viscometermentioning
confidence: 89%
“…Although the pure‐shear diffusion‐creep experiments of Kim et al. (2022) produced only A‐type and AG‐type LPO (girdled [100] and [001] within the shear plane), they predict that prolate (“cigar” shape) strain could promote the development of D‐type LPO. However, such constrictional strain in not expected at the base of the plate during corner flow, especially at fast spreading rates.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have proposed that olivine LPO in the upper mantle may be produced by diffusion creep, rather than dislocation creep or disGBS (Miyazaki et al, 2013;Yabe & Hiraga, 2020). Yabe and Hiraga (2020) observed grain sizes in mantle xenoliths from oceanic mantle lithosphere that follow the Zener relationship (Kim et al, 2022;Linckens et al, 2011), which can lead to grain sizes smaller than produced by steady state dynamic recrystallization -and therefore promote diffusion creep. Although the pure-shear diffusion-creep experiments of Kim et al (2022) produced only A-type and AG-type LPO (girdled [100] and [001] within the shear plane), they predict that prolate ("cigar" shape) strain could promote the development of D-type LPO.…”
Section: Interpretation Of D-type Fabricmentioning
confidence: 99%
See 1 more Smart Citation